2020
DOI: 10.21873/anticanres.14383
|View full text |Cite
|
Sign up to set email alerts
|

Primary and Interval Debulking Surgery Provide Similar Survival and Platinum Sensitivity Outcomes in Advanced Ovarian Cancer: A Retrospective Study

Abstract: Background/Aim: CHORUS and EORTC55971 trials demonstrated that neoadjuvant chemotherapy followed by interval debulking surgery (IDS) or primary debulking surgery (PDS) offered the same survival rates. These trials have since been criticised due to poor surgical complexity. We compared overall (OS), progression free (PFS), and platinum sensitivity in advanced ovarian cancer (AOC) patients undergoing IDS or PDS, who had received either intermediate or high complexity surgery to achieve complete cytoreduction. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In addition to large retrospective studies using national databases, our search yielded conflicting data from retrospective single institution studies comparing PDS to NACT. Of these studies, 13 showed no difference in survival between NACT and PDS [108][109][110][111][112][113][114][115][116][117][118][119][120][121][122][123], 16 studies showed better survival in the PDS group [124][125][126][127][128][129][130][131][132][133][134][135][136][137][138][139], and only 2 studies demonstrated superiority of NACT to PDS [140,141]. Our search yielded one prospective observational study showing better survival in the PDS group than NACT and one multiinstitutional retrospective study showing no difference in median OS but a higher risk of death at 2 years in the NACT group [142,143].…”
Section: Conflicting Data For Nactmentioning
confidence: 99%
“…In addition to large retrospective studies using national databases, our search yielded conflicting data from retrospective single institution studies comparing PDS to NACT. Of these studies, 13 showed no difference in survival between NACT and PDS [108][109][110][111][112][113][114][115][116][117][118][119][120][121][122][123], 16 studies showed better survival in the PDS group [124][125][126][127][128][129][130][131][132][133][134][135][136][137][138][139], and only 2 studies demonstrated superiority of NACT to PDS [140,141]. Our search yielded one prospective observational study showing better survival in the PDS group than NACT and one multiinstitutional retrospective study showing no difference in median OS but a higher risk of death at 2 years in the NACT group [142,143].…”
Section: Conflicting Data For Nactmentioning
confidence: 99%